Assessing individual running demands in position games: A comparison between official matches and different task sizes in young professional soccer players - Asian-Clemente, J. A.; Beltran-Garrido, J. V.; Requena, B. (European Journal of Sport Science, 2025)
The objectives of this study were to compare external loads between matches and position games based on player roles and to evaluate the load disparities between matches and different position games, individually considering each position. Twenty-five players (age: 21.9 ± 1.9 years; height: 177.9 ± 5.2 cm; weight: 75.5 ± 4.8 kg) were evaluated during 37 official matches and 18 position games classified according to their pitch sizes: small, medium, and large (50.8 ± 6.6 m2, 80.5 ± 4.6 m2, and 115.9 ± 25.2 m2 relative area per player, respectively). Players were categorized as: central defenders (CD), fullbacks (FB), defensive midfielders (CM), offensive midfielders (OM), wide midfielders (WM), and forwards (F). Using GPS, various metrics were recorded: distance covered (DC), DC > 21 km·h-1, peak speed, maximum accelerations and decelerations, and lower and higher than 3 m·s-2 (Acc<3; Acc>3; Dec<3; and Dec>3, respectively). Variables were normalized per minute (except peak speed, maximum accelerations, and decelerations). In all positions, matches consistently exhibited higher DC > 21 km·h-1 (p < 0.01), peak speed (p < 0.01), ACC<3 (p = 0.01), DEC<3 (p < 0.01), and maximum accelerations and decelerations (p < 0.01). Small and large formats showed the same disparities across all positions (p < 0.05), whereas in medium position games, this trend was observed exclusively among FB and F (p < 0.05). Position games displayed greater ACC>3 and DEC>3 than matches for certain player positions, but these depended on the size of the drill (p < 0.05). Position games present different external loads than matches, depending on the players' positions and the size of these tasks.